1957
DOI: 10.1177/019263655704122614
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Teaching: 1900-1955

Abstract: AS EDUCATION struggles to approach the status of a science, it is natural that inquiries should be directed into those configurations which may bring about successful teaching-and-learning situations. Almost every educational philosopher has his own cluster of fads, fancies, and facts concerning good teaching. The teacher, the parent, and the , pupil are often very practical in their criterion: if the pupil has learned well, then the teacher has taught well. Barr et al. (7, p. 642) says that &dquo;The ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Teachers' failure to apply constructivism as a method of learning has resulted in students not being able to form their own understanding in constructing analogies, examples and methods of digesting what they have learned in their own way [3]. Students are less interested in Science due to the teaching methods practised by teachers in the teaching and learning process of Science which are unable to draw their attention [1], [18], [27], [53], [57], [59]. Teachers only teach using traditional methods by giving descriptions and writing on the chalkboards.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' failure to apply constructivism as a method of learning has resulted in students not being able to form their own understanding in constructing analogies, examples and methods of digesting what they have learned in their own way [3]. Students are less interested in Science due to the teaching methods practised by teachers in the teaching and learning process of Science which are unable to draw their attention [1], [18], [27], [53], [57], [59]. Teachers only teach using traditional methods by giving descriptions and writing on the chalkboards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the concepts of contextual learning, mastery learning, inquiry and constructivism have been written in the Daily Lesson Plan, they are not fully implemented [48]. To address the problem of exam-based teaching and learning delivery methods, teacher-designed learning techniques should suit the various levels of the students' brainpower and be able to arouse their interest in learning Science topics easily and effectively [18], [27], [53], [57], [59]. Thus, it can be concluded that teaching methods and techniques play important roles in the teaching and learning process, where Science learning should be able to get students engaged in the teaching and learning process and even should enable them to identify problems, design problem solving methods and find solutions to such problems as in the Inquiry-Based Science Education (IBSE) strategy [25], [44], [46], [1], [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This opinion is not uncommon today. Dodes (12), reviewing studies from 1900-1955 in order to suggest measures for solidifying the background of pedagogical knowledge, concluded that the dearth of scientific evidence is the result, in part, of ready acceptance of mere opinion and of a lack of clarity in terminology. The need to study teacher behavior in a context of theory was emphasized by Ryans (47), and it is this recurring theme which justifies inclusion of a chapter on teaching in this issue of the REVIEW.…”
mentioning
confidence: 99%